Metaphor as a mechanism of invalidating gender stereotypes - Smirnov, Ivan (Вопросы семантики и стилистики текста: лингвистический дискурс, 2021)
The article challenges the theoretical claims of gender linguistics. The androcentric point of view that is dominant in gender studies is especially challenged. The initial material for the analysis was the metaphorical nominations characterizing a male in Chinese. The equivalents given in Russian confirm the existence of common motivational attitudes reflected in the Chinese and Russian languages. An alternative view of the proposed representational schemes contributes to the rejection of stereotypes established in gender studies.